Mystery in parotid - Mohanapriya, T.; Karthikeyan, T. P.; Singh, K. Balaji; Arulappan, T. (International Surgery Journal, 2017)
Background: Parotid gland is the largest of the salivary glands present in the body. Neoplastic lesions in parotid gland always causes difficulty in tissue diagnosis due to their diversified histology. Lesion in the superficial lobe of parotid is more amenable for clinical diagnosis but deep lobe lesion requires imaging to confirm the diagnosis. Managing parotid swelling seems like a mystery due to these issues. Methods: There were 30 patients who presented with complaints of swelling in the parotid region. For all these patients detailed history was taken and clinical examination was done and findings noted. Contract enhanced computed tomography (CECT) of the parotid region was done followed by fine needle aspiration cytology (FNAC) and the management was planned accordingly. Results: All the 30 patients were within the age group of 25 years to 65 years. All the patients presented with swelling in the parotid region. Among the 30 patients, 10 patients had complaints of associated pain in the parotid region. On clinical examination, all the patients had lesion in the superficial lobe of parotid and 2 patients had deep lobe involvement. 1 patient had features of facial nerve palsy. Contrast enhanced computed tomography (CECT) and Fine needle aspiration cytology (FNAC) was done. For all the patients’ surgical management was planned accordingly. Conclusions: Routinely submitting all parotid swelling patients to Fine needle aspiration cytology and computed tomography helps to solve the mystery of diversified histology and presentation.